(untitled) (Research, Society and Development, 2021)
Objective: to analyze the trend of Brazilian scientific production about the therapeutic potential of Rosemary for health Methodology: this is an integrative literature review with a bibliographic survey carried out from December 2020 to January 2021, in the Digital Library of Theses and Dissertations: BDTD and in the Theses and Dissertations Catalog (CAPES). 682 productions were found, of which 71 were analyzed. Data collected using an instrument developed by the authors and analyzed based on the identification of similarities, differences and inferences. Results: 70.4% of the total productions were dissertations and 29.6% theses, most from graduate programs in Pharmaceutical Sciences and Veterinary, 54.9% researches were developed in vitro, 35.2% in vivo (two included humans). As for the effects of Rosemary or its compounds, 59.2% analyzed the antimicrobial and antibiofilm effects, 19.7% the anti-inflammatory, 16.9% the antioxidant activity, 12.7% the cell viability and cytotoxicity, among others. Product development surveys totaled 15.5%. Final Considerations: there is a growing trend of Brazilian scientific production about the therapeutic potential of Rosemary for health, with the involvement of several universities in the country. The lack of research from Graduate Nursing Programs opens doors for their inclusion in the subject. The studies tended to evaluate the antimicrobial and antibiofilm action of Rosemary and its compounds, followed by the anti-inflammatory and antioxidant effect, showing therapeutic potential against microorganisms and for chronic diseases. More research on the subject is needed, including with a view to product development.